Mast cells in the bone marrow microenvironment - Ribatti, Domenico (Frontiers in Immunology, 2026)
The bone marrow microenvironment provides the necessary signals for the development from hematopoietic stem cells into mast cell precursors. Once released in the bloodstream, mast cells quickly migrate to peripheral tissues where they complete their differentiation. Mast cells are located at the interface with the external environment, therefore are among the first cell types that can get in contact with pathogens. Mast cells are found in every tissue, most abundantly near barriers where they exert the role of immune sentinels during both acute and chronic inflammation. Mast cells are known for their effects when eliciting immediate hypersensitivity reactions. However, they are involved in numerous other physiological and pathological conditions such as those that occur in bone marrow microenvironment, as has been discussed in this article.